The Assessment Instrument Development of Muhammadiyah Da'wah Strategy - Subando, Joko; Samsuri, Muh.; Rohimah, Siti; Mulyanto, M; Anshori, Isa (Universitas Muhammadiyah Surakarta, 2023)
This research aims to develop an assessment instrument for Muhammadiyah da'wah strategy. This research is developed research by adapting Borg and Gall's development research steps. The research activity begins by analyzing books and articles related to Muhammadiyah to gain the instrument construct. The construct is utilized to be a basis for compiling a prototype instrument which is then validated by 5 experts consisting of measurement experts (2 people), Muhammadiyah ideology experts (2 people) and language expert (1 person) to get an idea of the suitability of variables with indicators and the suitability of indicators with statements. The next stage is a limited trial that involves 25 people from the regional leader of Muhammadiyah Karanganyar. It is then continued to an expanded trial that involves 322 respondents from the regional leader of Muhammadiyah Karanganyar, Sragen, and Boyolali. Data from limited trial are analyzed by using EFA, while data from expanded trial are analyzed by using CFA. This research succeeds in developing an assessment instrument of Muhammadiyah da'wah strategy. The number of items and aspects measured include aspects of community development (5 items), life quality improvement (5 items), cadres strengthening (9 items), association strengthening (6 items), and political and state strategies (6 items) so that there is a total of 31 items. The instrument has guaranteed content validity that is shown by the calculated v aiken value of 0.933-1.00 (>0.933). It also has guaranteed construct validity that is shown by the factor loading value for each statement item ranging from 0.61-0.93 (> 0.5). The instrument also has a guaranteed reliability instrument that is shown by the construct reliability (CR) value of 0.620-0.964 (>0.6). The measurement model is considered to be a feasible model because it meets 7 criteria, namely calculated chi square/df (1.40<2), RMR (0.029<=0.05), RMSEA (0.052<=0.08), NFI (0.96>=0.9), NNFI (0.98>=0.9), CFI (0.99>=0.9), IFI (0.99>0.9). With the presence in a guarantee of validity and reliability as well as the feasibility of the measurement model, the instrument can be used to measure the accuracy of Muhammadiyah da’wah strategy.